The evidence for excess risk of cancer and non-cancer disease at low doses and dose rates - Simon, SL; Kendall, GM; Bouffler, SD; Little, MP (Radiation Research Society, 2022)
The question of whether there are excess radiation-associated health risks at low dose is controversial. We present evidence of excess cancer risks in a number of (largely pediatrically or in utero exposed) groups exposed to low doses of radiation (<0.1 Gy). Moreover, the available data on biological mechanisms do not provide support for the idea of a low-dose threshold or hormesis for any of these endpoints. There are emerging data suggesting risks of cardiovascular disease and cataract at low doses, but this is less well established. This large body of evidence does not suggest and, indeed, is not statistically compatible with any very large threshold in dose (>10 mGy), or with possible beneficial effects from exposures. The presented data suggest that exposure to low-dose radiation causes excess cancer risks and quite possibly also excess risks of various non-cancer endpoints.